Adolescents' Psychological Functioning at School and in Sports: The Role of Future Time Perspective and Domain-Specific and Situation-Specific Self-Determined Motivation - Mouratidis, Athanasios; Lens, Willy (Journal of Social & Clinical PsychologyJournal of Social & Clinical Psychology, 2015)
In two short-term diary studies, conducted in an educational and a sport context, we investigated whether adolescents' domain-specific and situation-specific self-determined motivation, along with future time perspective, could explain intrapersonal variation of and interpersonal differences in psychological functioning. In both studies intrapersonal fluctuation of self-determined motivation related positively to desired outcomes, with perceived autonomy operating as a predictor of situation-specific self-determined motivation (Study 2). Moreover, in both Study 1 ( N = 57 high-school students) and Study 2 ( N = 63 athletes participating in a three-week basketball camp) we found interpersonal differences in domain-specific autonomous motivation and future time perspective to predict positively mean levels of most of the positive outcomes. These results underscore the key role of self-determined motivation and future time perspective in the prediction of psychological functioning and the importance of looking not only at the interpersonal differences but also at the underlying motivational dynamics operating at the within-person level. [ABSTRACT FROM AUTHOR]Copyright of Journal of Social & Clinical Psychology is the property of Guilford Publications Inc. and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission. However, users may print, download, or email articles for individual use. This abstract may be abridged. No warranty is given about the accuracy of the copy. Users should refer to the original published version of the material for the full abstract. (Copyright applies to all Abstracts.)
Keywords: adolescence; ADOLESCENT psychology; AUTONOMY (Psychology); BASKETBALL camps; diary study; future time perspective; MOTIVATION (Psychology); psychological functioning; Self-determination theory; TEENAGERS -- Attitudes; TIME perspective